The effect of nitrido, azide, and nitrosyl ligands on magnetization densities and magnetic properties of iridium PNP pincer-type complexes. Issue 102 (5th October 2015) - Stuart, Daniel; Tecmer, Paweł; Ayers, Paul W.; Boguslawski, Katharina
Abstract : The magnetisation density of different iridium PNP pincer-type complexes depends on the chosen quantum chemistry method. Abstract : We present a systematic theoretical study of electronic structures, magnetization densities, and magnetic properties of iridium PNP pincer-type complexes containing non-innocent nitrido, azide, and nitrosyl ligands. Specifically, the quality and accuracy of density functional theory (DFT) in predicting magnetization densities obtained from various approximate exchange–correlation functionals is assessed by comparing them to complete active space self-consistent field (CASSCF) reference distributions. Our analysis points to qualitative differences in DFT magnetization densities at the iridium metal center and the pincer ligand backbone compared to CASSCF reference data when the non-innocent ligands are changed from nitrido, to azide, to nitrosyl. These observations are reflected in large differences in hyperfine couplings calculated for the iridium metal center.